Isolation and identification of phytate-degrading yeast from traditional fermented food - Ade Erma Suryani; AYU SEPTI ANGGRAENI; LUSTY ISTIQOMAH; EMA DAMAYANTI; MOHAMMAD FAIZ KARIMY (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Suryani AE, Anggraeni AS, Istiqomah L, Damayanti E, Karimy MF. 2021. Isolation and identification of phytate-degrading yeast from traditional fermented food. Biodiversitas 22: 866-873. Application of phytase (myo-inositol hexakisphosphate phosphohydrolase) to catalyze the release of phosphate from phytates contained on grain-based feed has been used widely in poultry feed industry. In this study, yeast as phytase producer from traditional fermented food was isolated, screened and identified their morphological, biochemical, and molecular characteristics. Production of extracellular phytase from yeast was quantified using spectrophotometer. The results showed that among 8 yeast isolates that had phytase activity, there were two isolates with the highest phytase activity and specific activity which were TKd3 isolate (6.57 U/mL and 54.230 U/mg) and GF1 (6.07 U/mL and 53.68 U/mg). Morphological identification using Scanning Electron Microscope revealed that TKd3 cells isolated from soybean tempeh had an elongated oval cell structure, whereas the GF1 isolated from fresh gatot had a rounder cell structure. TKd3 isolate with accession number MW131530 had homology with Candida tropicalis ATCC 750 28S rRNA with 99.83% similarity and GF1 isolate with accession number MW131531 had homology with Candida tropicalis ATCC 750 28S rRNA with 100% similarity. It could be concluded that C. tropicalis yeast from traditional fermented food produced the extracellular phytase for further use of phytase in poultry feed additive.